Peran Bimbingan Rohani Islam dalam Membentuk Spiritualitas Orang dengan Gangguan Jiwa (ODGJ) di RPS PMKS Pamardi Raharjo Banjarnegara - Umi Fadlilah; Aedi, Ulul (Sociocouns: Journal of Islamic Guidance and Counseling, 2025)
Islamic Spiritual Guidance is a positive activity that can have a positive impact on patients with mental disorders who are undergoing the rehabilitation process in mental institutions. Islamic spiritual guidance has a good aim for patients. Islamic spiritual guidance is expected to provide direction and knowledge regarding the patient's religion and beliefs. So that when they return to society they can be well received by other members of society. Therefore, researchers made observations related to the Islamic spiritual guidance implemented at the orphanage. The research uses qualitative research methods, namely by observing patients while taking part in spiritual guidance activities. From the observations, results were obtained which stated that Islamic spiritual guidance could better shape the spirituality of patients in these institutions.